Design of Ku‐band GaN HEMT power amplifier based on multi‐bias statistical model. (1st December 2015) - Chen, Zhikai; Xu, Yuehang; Wang, Changsi; Wen, Zhang; Xu, Ruimin
Abstract: A design method for microwave GaN high‐electron mobility transistor (HEMT) power amplifier based on equivalent circuit parameters multi‐bias statistical models is presented. The statistical modeling method includes principal component analysis, factor analysis, and multiple regressions modeling techniques. The statistical model is validated by comparing original and Monte Carlo‐simulated means, standard deviations, correlation matrix, and S‐parameters. A Ku‐band GaN HEMT power amplifier is designed with high drain efficiency by using the established statistical model for demonstration purpose. The simulated results are statistically indistinguishable from the measured results. This method is suitable for GaN HEMT power amplifier design and yield analysis. Copyright © 2015 John Wiley & Sons, Ltd.